Optical absorption and XPS studies of (Ba1-xSrx)(Ce0.75Zr0.10Y0.15)O3-delta electrolytes for protonic ceramic fuel cells - Jaiswal, Shivendra Kumar; Hong, Jongsup; Yoon, Kyung Joong; Son, Ji-Won; Lee, Hae-Weon; Lee, Jong-Ho (ELSEVIER SCI LTD, 2016)
Perovskite-type materials containing metal and cerium cations have been used as catalysts, membranes, electrodes in fuel cells, and hydrogen pumps. The effect of strontium doping on the perovskite-type structure has been evaluated and effectively maintains the cubic structure of (Ba1-xSrx)(Ce0.75Zr0.10Y0.15)O3-delta. X-ray photoelectron spectroscopy (XPS) was performed on the oxidation states of barium, strontium, cerium, zirconium, yttrium and oxygen. With strontium doping, the oxidation state of cerium ions in 4+ increases and results in the decrease in oxygen vacancy concentration. These are attributed to the strong binding energy of (A/B)-O bond which in turn, enhances the structural stability of electrolyte system. The free volume (V-f) is maximum for x=0.2 (V-f=33.1 angstrom(3)) and then decreases with further strontium insertion. The optical absorption peaks are attributed to charge transfer transitions and energy band gap (increases from similar to 4.13 to similar to 4.35 eV). However, the increase of band gap is only similar to 5% with partial replacement of barium by strontium. These characteristics are useful to make (Ba1-xSrx)(Ce0.75Zr0.10Y0.15)O3-delta a promising candidate for futuristic and reliable fuel cell technology. (C) 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: OXIDE; CONDUCTIVITY; DEGRADATION; STABILITY; OXIDATION; MEMBRANE